2014
DOI: 10.1175/jtech-d-13-00174.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the New Version of the Laser-Optical Disdrometer, OTT Parsivel2

Abstract: A comparative study of raindrop size distribution measurements has been conducted at NASA’s Goddard Space Flight Center where the focus was to evaluate the performance of the upgraded laser-optical OTT Particle Size Velocity (Parsivel2; P2) disdrometer. The experimental setup included a collocated pair of tipping-bucket rain gauges, OTT Parsivel (P1) and P2 disdrometers, and Joss–Waldvogel (JW) disdrometers. Excellent agreement between the two collocated rain gauges enabled their use as a relative reference fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
196
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(206 citation statements)
references
References 21 publications
6
196
0
4
Order By: Relevance
“…IFloodS Xband radar data is publicly available in Krajewski et al (2016). IFloods Parsivel data is publicly available in Petersen et al (2014). Table A3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…IFloodS Xband radar data is publicly available in Krajewski et al (2016). IFloods Parsivel data is publicly available in Petersen et al (2014). Table A3.…”
Section: Discussionmentioning
confidence: 99%
“…The scans covered the region over three of the disdrometers. The third data set was from a network of 14 Parsivel 2 disdrometers (Petersen et al, 2014) deployed in Iowa, US, during the National Aeronautics and Space Administration Iowa Flood Studies (IFloodS) Global Precipitation Measurement ground validation campaign. Overlooking this network was the University of Iowa's X-band radar XPOL5 .…”
Section: Double-moment Dsd Normalisationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, two generations of this model have been installed over time; the oldest station is of the first generation (marked in italics on the map. It was shown that the second generation was an improvement over the first generation for both drop size and rainfall measurements [35]. This network was initiated in 2004 (Alès station, [30]) and was densified during the HyMeX project, whose special observation period (SOP) took place in 2012 [33].…”
Section: Disdrometers Networkmentioning
confidence: 99%